Prevalence and Pattern of Smoking among Bus Drivers of Dhaka, Bangladesh - Goon, Shatabdi (Tob Use Insights, 2014)
BACKGROUND: Smoking is an increasingly prevalent habit in Bangladesh, particularly among men with low socioeconomic status. AIM: The aim of this study was determining the prevalence and pattern of smoking among bus drivers of Dhaka city, Bangladesh. METHODS: A cross-sectional study was carried out from 15 to 26 March 2013 among four hundred bus drivers of Dhaka city, Bangladesh aged between 18 and 50 determining the prevalence, pattern, and socioeconomic determinants of smoking. Data were input into a pre-designed access database with data management and analysis using standard statistical tools (SPSS-15) to assess significance through cross-tabulation. RESULTS: The overall prevalence of smoking among bus drivers was 93%, and 20% of their daily income was spent on smoking. Though most (32.3%) of the drivers started smoking before involving in driving profession, but excessive smoking had been promoted by occupational and environmental stress experiencing hectic work schedule. Individuals with no education were three times (odds ratio (OR) 2.8; 95% CI 1.2–6.13) more likely to be smoker. Smoking was detected among 53.2% of smokers aged 26 or above (χ(2) = 8.30, P < 0.05), and they showed significantly high prevalence. The reasons behind smoking were almost exclusively habit (38.1%), peer influence (26.8%), and thinking of stress relief (25.3%). Smoking can also worsen poverty among users and their families because most of the drivers reported chest pain (34.4%), heart disease (25.8%), and other health complications caused by smoking depriving families of much-needed income and imposing additional costs of health care. CONCLUSION: Interventions and preventions by policy makers, public health experts, and other stakeholders should be introduced considering high prevalence of smoking among Bangladeshi bus drivers with detrimental health sequel.